High-volume pre-dilution on-line hemodiafiltration is the adequate blood purification method from the viewpoint of amino acid nutrition - Kato, Motoko; Urabe, Shunichiro; Matsuzawa, Shohei; Kato, Akira; Fukazawa, Momoko; Hiyama, Emi; Kurii, Asami; Mikami, Noriko; Kitajima, Yukie; Hida, Miho; Kokubo, Kenichi; Hyodo, Toru (Renal Replacement Therapy, 2022)
Background We compared amino acid leakage among high-volume pre-dilution on-line hemodiafiltration (Pre O-HDF), hemodialysis (HD), and post-dilution on-line hemodiafiltration (Post O-HDF). Subjects and methods The subjects were 9 patients. For HD, the total dialysate flow rate was established as 500 mL/min. For high-volume Pre O-HDF, it was established as 600 mL/min, under a replacement fluid volume of 90 L. For Post O-HDF, it was established as 600 mL/min, under a replacement fluid volume of 10 L. In both procedures, the duration of treatment was 4 h, and the blood flow volume was 200 mL/min. We compared the leakages of total amino acid, non-essential amino acid, and essential amino acid, clear spaces (CSs), β 2 -microglobulin (β 2 -MG) reduction rate, Kt/V for urea, and albumin leakage among the three procedures. Results Amino acid leakages after high-volume Pre O-HDF were significantly lower than HD and Post O-HDF. The CSs after high-volume Pre O-HDF were significantly lower than Post O-HDF. The β 2 -MG reduction rate after high-volume Pre O-HDF was significantly lower than Post O-HDF. The Kt/V for urea was not significantly different. Albumin leakages were below the detection limit (< 1 g) in the three procedures. Conclusion Under the treatment conditions we performed this time, high-volume Pre O-HDF reduces amino acid leakage in comparison with HD and Post O-HDF. High-volume Pre O-HDF is a therapeutic mode that suppresses amino acid leakage.